Method for producing binder phase reinforced cemented carbide materials

JP2024518385A5Pending Publication Date: 2025-04-28BETEK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023568000
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-08-04
Filing Date
2022-04-21
Publication Date
2025-04-28

AI Technical Summary

Technical Problem

The existing cemented carbides have a decrease in the strength of metal bonding agent under high temperature conditions, which leads to wear and corrosion of the bonding agent layer, affecting the wear resistance and crushing strength of the tool.

Method used

By introducing intermetallic compound phase materials, especially the combination of Ni and Al, the (M,Y)3(Al,X) structure is formed, the thermal stability and strength of the bonding agent are enhanced, and the intermetallic compound phase materials are formed by heat treatment or frictional heat during use using tools.

Benefits of technology

It significantly improves the wear resistance and crushing strength of cemented carbide, especially under high temperature conditions, enhances the wear resistance and corrosion resistance of the bonding agent, and extends the service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a sintered carbide material, in particular a hard alloy, comprising 70-95% by weight, advantageously 80-95% by weight, of tungsten carbide in dispersed form and a binder phase, the binder phase comprising a metallic binder material, which comprises Co, the binder phase comprising intermetallic phase material and / or dissolved elements Ni and Al, the intermetallic phase material, if present, being formed according to the structural formula (M,X)3(Al,Y), where M=Ni, Y=Co and / or other components, X=tungsten and / or other components, the binder phase having the following chemical element composition: Ni>25% by weight, Al>4% by weight, balance Co and dissolved binder components, e.g. W and / or C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cemented carbide material, in particular a hard alloy, comprising 70-95% by weight of tungsten carbide in dispersed form and a binder phase, the binder phase comprising a metallic binder material, in particular Co.

[0002] EP 2 691 198 describes such a cemented carbide material, i.e. a hard alloy body, and a method for its production. According to this known method, a powder containing coarse-grained tungsten carbide and a larger than stoichiometric proportion of carbon and cobalt powder is mixed. Powdered tungsten is then added to this powder. The tungsten powder and the cobalt powder had an average grain size of about 1 μm. The coarse-grained tungsten carbide had an average grain size of 40.8 μm.

[0003] The powder was then ground in a ball mill, to which hexane and paraffin wax were added. A green compact was produced from the mixture by pressing, and the green compact was then sintered. After the sintering process, the resulting sintered carbide material was subjected to a heat treatment, where it was heated to 600°C and held at this temperature for 10 hours.

[0004] After a subsequent cooling step, the sintered carbide material was subjected to analysis, where it was found to have nanoparticles in the binder phase, the nanoparticles having a size of less than 10 nm. The nanoparticles were formed by eta phase (Co3W3C) or (Co6W6C) or theta phase (Co2W4C). The grain size of the nanoparticles was less than 10 nm.

[0005] Nanoparticles have been found to be associated with a strengthening of the binder phase, which can increase the hardness of cemented carbide materials. The drawback of these materials is the lack of thermal stability of nanoparticles, which makes them only suitable to a limited extent for high temperature applications or applications where high temperature inputs occur.

[0006] During rock processing and cutting of asphalt and concrete, friction generates very high temperatures on the tool surface. The hard material tungsten carbide is not significantly affected by these temperatures, as it has a high hot hardness even at these temperatures. However, the strength of the metal binder decreases dramatically at these temperatures. When the strength of the metal binder decreases, the stresses of use result in increased wear and tear and dissolution of the binding phase. As a result, the tungsten carbide grains can no longer be held in the hard alloy.

[0007] The object of the present invention is to provide a sintered carbide material, in particular a hard alloy, which has improved wear resistance and at the same time high fracture strength.

[0008] This problem is solved by the features of claim 1. Thereby, a sintered carbide material, in particular a hard alloy, is proposed which comprises 70-95% by weight, advantageously 80-95% by weight, of tungsten carbide in dispersed form and a binder phase, the binder phase comprising a metallic binder material, which comprises Co, the binder phase comprising intermetallic phase material and / or dissolved elements Ni and Al, the intermetallic phase material, if present, being formed according to the structural formula (M,X)3(Al,Y), where M=Ni, Y=Co and / or other components, X=tungsten and / or other components, the binder phase having the following chemical element composition: Ni>25% by weight, Al>4% by weight, remainder Co and dissolved binder components, e.g. W and / or C.

[0009] The invention therefore proposes cemented carbide materials, in particular hard alloys, which have and / or are prepared to form a reinforcing binder phase, in each case being reinforced by an intermetallic phase material.

[0010] If the intermetallic phase material is already present in the binder phase, the intermetallic phase material directly strengthens the binder phase.

[0011] When the cemented carbide material in the binder phase contains the dissolved elements Ni and Al, heat treatment of the cemented carbide material forms intermetallic phase material which then strengthens the binder phase.

[0012] During this heat treatment, the binder phase elements Ni, Co, W and Al combine to form an intermetallic phase material according to the structural formula (M,Y)3(Al,X), where M=Ni, Y=Co and / or other elements, and X=Tungsten and / or other elements.

[0013] Here, heat treatment of the cemented carbide material can be accomplished in a variety of ways suitable for predictably forming the intermetallic phase material.

[0014] Here, in particular, it may be a heat treatment, in particular the introduction of heat from the outside into the sintered carbide material. The heat treatment may, for example, be caused by an active source generating heat or cold, which is introduced into or removed from the material. Thus, for example, the formation of the intermetallic phase material may take place in a furnace into which the sintered carbide material is introduced. It is also conceivable to expose at least a part of the surface of the sintered carbide material to a heating device, for example a burner.

[0015] It is also contemplated that there is an excitation source that introduces energy into the cemented carbide material to generate heat in the cemented carbide material, which may be, for example, an induction coil or a laser device.

[0016] It is also conceivable that heat is generated by passive heating, i.e. by using the sintered carbide material, preferably during expected operating conditions or during the processing, in particular the method steps in which the sintered carbide material is utilized.

[0017] Here, heat is generated in the cemented carbide material, for example by friction, as occurs, for example, during the intended use of the cemented carbide material, in particular during the intended use, in particular during the use of a tool, which in the case of a tool is moved relative to the workpiece (for example, in the case of a road cutting chisel, the road cutting chisel relative to the road surface), which generates frictional energy, which in turn generates heat in the cemented carbide material. The heat generated in this way can be used to achieve a self-reinforcing effect of the binder phase by at least partial formation of intermetallic phase material in the cemented carbide material.

[0018] It is also conceivable that the cemented carbide material is passively heated during the process step in which it is applied to a substrate, for example a tool base or carrier, and the heat generated in this case can be used to form intermetallic phase materials. Possible joining methods here are welding methods, for example friction welding, electron beam welding, brazing methods, for example hard brazing, furnace brazing, induction brazing, diffusion brazing, cladding methods, for example explosive bonding.

[0019] In order to achieve the above mentioned effects, according to the invention it is provided that the bonding phase has the following chemical element composition: Ni>25 wt.%, Al>4 wt.%, balance Co and dissolved binder components such as W and / or C.

[0020] The intermetallic phase material forms crystalline intercalations in the metallic binder.

[0021] This intermetallic phase material has significantly higher strength, especially at high temperatures, than the metallic binder material it is intercalated in. At the surface of the cemented carbide material subjected to wear attack, the intermetallic phase material reduces erosion and dissolution of the metallic binder material, for example when used in earth-excavating tools.

[0022] The movement of the earth-digging tool and the loosened and remaining soil materials cause abrasive and mechanical loads on the cemented carbide material, where the tungsten carbide grains are sufficiently resistant to this abrasive attack. The problem in the prior art is that the strength of the binder material is significantly lower than that of tungsten carbide. Now, according to the invention, the intermetallic phase material is incorporated or formed in the binder phase, so that rapid erosion and dissolution of the metallic binder material is prevented.

[0023] Moreover, it has surprisingly been found that the internal structure of the cemented carbide material can also be strengthened by the intermetallic phase material. In the event of strong shock-like stresses, the crystals of the intermetallic phase material reduce or prevent the sliding of the tungsten carbide particles in the region of the binder phase connecting the tungsten carbide particles and thus the excessive plastic deformation of the binder phase. In particular, in this case, the individual crystals of the intermetallic phase material support each other. This is of great advantage, in particular, at high tool operating temperatures, because at these temperatures the strength of the Co in the binder phase is reduced, but the intermetallic phase material still ensures that it provides sufficient support for the binder material.

[0024] Overall, it has been found that the solution according to the invention allows a significant increase in the wear resistance of sintered carbide materials to be achieved. For example, tests have shown that when sintered carbide materials according to the invention are used in the form of cutting tips in round shank chisels for road milling machines, the wear resistance can be increased by up to 50%. It has been found that such a significant increase in wear resistance can be achieved when milling asphalt and concrete road surfaces.

[0025] The sintered carbide material according to the invention can in particular be used to construct the working area of ​​tools for the treatment, loosening, transport and processing of plant, mineral or building materials, in particular in the fields of agriculture, forestry or road construction, mining or tunnel construction.

[0026] If intermetallic phase materials are present in the sintered carbide material, then according to one variant according to the invention it can be provided that the proportion of metallic binder material in the sintered carbide material is 1-28% by weight, preferably 1-19% by weight, whereby the entire or almost entire proportion of this metallic binder material, apart from unavoidable impurities, can be formed by Co. Such a material selection results in a particularly tough binder phase, which is effectively reinforced by existing or emerging intermetallic phase materials.

[0027] According to one variant of the invention, it can be provided that the sum of the elements Ni and Al in the cemented carbide material is between 1 and 28% by weight, advantageously between 1.5 and 19% by weight, at least in one region of the cemented carbide body. This range of data takes into account both the Ni and Al of the intermetallic phase material that may be present, and also Ni or Al dissolved in the binder phase. Such a composition makes it possible to manufacture earth-digging tools made of hard alloys, which place particularly high demands on them.

[0028] If no or only little intermetallic phase material is present in the sintered carbide material, it can be provided according to one variant of the invention that the proportion of binder phase in the sintered carbide material is 5-30% by weight, advantageously 5-20% by weight. In this case, the majority of the binder phase may be formed by the metallic binder material Co. Furthermore, Al and Ni may be dissolved in the binder phase as metallic binder materials. Finally, further elements and unavoidable impurities may also be present in the binder phase.

[0029] According to the invention it can also be provided that, apart from unavoidable impurities, the binder phase contains other elements besides Co, Ni, Al, in particular dissolved W, C and / or Fe.

[0030] In accordance with the present invention, the intermetallic phase material optionally present in the binder phase is formed according to the structural formula (M,Y)(Al,X) or can be formed according to this structural formula based on the elemental composition in the finished cemented carbide material, where M=Ni, Y=Co and / or other components, and X=Tungsten and / or other components.

[0031] When intermetallic phase material is present in the binder phase, it is advantageous that, at least in the majority of the crystals of the intermetallic phase material, Y=Co and X=W. The composition of the soluble constituents in the binder phase in the cemented carbide material is therefore selected so that the intermetallic phase material can thus form by heat treatment or the action of heat (see above).

[0032] Furthermore, for some or all of the crystallites of the intermetallic phase material (Al,X), X can be present not only in the form of W, but also in the form of Mo and / or Nb and / or Ti and / or Ta and / or Cr and / or V. The composition of the dissolved constituents in the binder phase in the finished cemented carbide material can therefore be selected such that the intermetallic phase material can thus form by heat treatment or the action of heat (see above).

[0033] According to the invention it is possible to provide that the binder phase comprises two or more intermetallic phase materials or only a single intermetallic phase material and / or that the cemented carbide material is prepared such that two or more intermetallic phase materials or only a single intermetallic phase material are formed by heat treatment or the action of heat.

[0034] According to a preferred embodiment of the invention, the binder phase has the following chemical element composition: Ni>35wt%, Al>5wt%, balance Co and dissolved binder components such as W and / or C; Particularly preferred is Ni>40, Al>6.5 wt.%, balance Co and dissolved binder components such as W and / or C. It is possible to provide for the device to have the following:

[0035] Here, these data relate to the total content of the respective substances in the binder phase, therefore taking into account not only the elements in dissolved form but also those present in a bonded state in the intermetallic phase material.

[0036] The specified data values ​​were found to provide the optimum reinforcing effect of the binder phase.

[0037] In order to be able to produce an optimal strengthening of the binder phase by the intermetallic phase material, it is possible within the scope of the invention to provide that the ratio of the weight fraction of Al to the weight fraction of Ni is >0.10, advantageously >0.12.

[0038] It can advantageously be provided here that the ratio of the weight proportion of Al to the weight proportion of Ni is ≦0.46, advantageously ≦0.18, particularly preferably ≦0.16.

[0039] The above data on the ratio of the weight percentage of Al to the weight percentage of Ni considers the total weight percentages, i.e. both the dissolved elements Al and Ni and the Al and Ni in the intermetallic phase material (if present). The detection of the weight percentages of Al and Ni can be carried out by conventional ICP measurements.

[0040] A possible variant of the invention is that the cemented carbide material has at least two volume regions, the first volume region being configured such that the relative proportion of intermetallic phase material per unit volume is greater than in the second volume region. The configuration of at least two volume regions allows targeted influence of the properties of the cemented carbide material, in particular the tool properties. For example, a zone exposed to high levels of wear and abrasion can have a volume region with a high relative proportion of intermetallic phase material. In contrast, a zone that has to meet special toughness requirements can have a volume region with a low relative proportion of intermetallic phase material. For the sake of completeness, it is pointed out here that the second volume region, which has a low relative proportion of intermetallic phase material compared to the first volume region, may also be free of intermetallic phase material.

[0041] In one possible alternative form of the invention, the first volume region having a high relative proportion of intermetallic phase material is arranged to be bounded by at least one region of the surface of the cemented carbide material, thus creating a high wear resistance at the surface of the cemented carbide material. Advantageously, the second volume region is not located adjacent to the surface of the cemented carbide material, but is present in the interior of the cemented carbide material, thereby ensuring a high fracture stability.

[0042] It can also be provided that the second volume region, which has a lower relative proportion of intermetallic phase material compared to the first volume region or is free of intermetallic phase material, borders at least one region of the surface of the cemented carbide material, and preferably the first volume region is not adjacent to the surface of the cemented carbide material. This makes it possible to produce a tool whose cutting contour is optimally adapted to the cutting task during use of the tool in order to achieve an optimal life. In particular, a so-called resharpening effect can be realized.

[0043] A possible variant of the invention is that the binder phase, in particular the metallic binder material and / or the intermetallic phase material, comprises Nb and / or Ti and / or Ta and / or Mo and / or V and / or Cr, advantageously one or more of these materials being present in the binder phase in dissolved form and / or in the form of carbides. This allows an increase in the solvus temperature and strength of the existing intermetallic phase material and / or of the intermetallic phase formed by the action of heat or heat treatment to be achieved. As a result, less intermetallic phase material is required while the strength of the sintered carbide material remains the same. Alternatively, the addition increases the binder strength and thus the hot strength.

[0044] However, it is also contemplated that one or more of the aforementioned components are incorporated into at least a portion of the crystal lattice of the intermetallic phase material, or can be incorporated into the crystal lattice of the intermetallic phase material by thermal treatment (heat treatment or the action of heat). For example, titanium atoms (or another member of the aforementioned group) will occupy primarily Al or W lattice sites in the crystal lattice of the intermetallic phase material, and similarly to W, will increase the precipitation temperature of the intermetallic phase material.

[0045] Thereby, if intermetallic phase materials are present in the cemented carbide material, on the one hand, they can be precipitated more effectively during the sintering process, since precipitation starts already at high temperatures, since in this case the diffusion rates are significantly higher.

[0046] On the other hand, as already mentioned, higher hot strength is achieved by this measure, since the solvus temperature of the cemented carbide material is increased, in other words the temperature required to be able to re-melt the intermetallic phase material in the cemented carbide material is increased.

[0047] According to the invention, it is also possible to provide that the proportion of Mo and / or Nb and / or Ti and / or Ta and / or Cr and / or V in the binder phase is ≦15 at%. The abovementioned elements do indeed form carbides in principle. Within the scope of the invention, it is now possible to provide that the material composition is selected such that these elements are dissolved in small amounts in the binder phase depending on their solubility product and their affinity for carbon, so that they can be incorporated into the crystal lattice of the intermetallic phase material and / or that they can dissolve in the metallic binder phase. If a sintered carbide material with a high toughness of the binder phase is desired, it is desirable to limit the proportion of carbide forms to small amounts. In that case, it is desirable for the material to be present in a total proportion of ≦15 at%.

[0048] Furthermore, it is advantageous that the powder mixture for the production of the cemented carbide material can be stoichiometrically adjusted with respect to the carbon proportion, since titanium (and / or Mo and / or Nb and / or Ti and / or Ta and / or Cr and / or V) takes over the role of tungsten.

[0049] According to one variant of the invention, it can be provided that the carbon proportion is adjusted to be stoichiometric or less than stoichiometric. This measure prevents or minimizes graphite precipitation in the sintered mass, which would be caused by a carbon proportion greater than stoichiometric. The inventors have recognized that such intercalation has a detrimental effect on the fracture strength of the sintered carbide material.

[0050] According to the invention, the carbon percentage in the cemented carbide material is C 化学量論量 (wt%) - 0.003 × binder content (wt%) to C 化学量論量 (wt%) - up to 0.012 x binder content (wt%) and advantageously in the range C 化学量論量 (wt%) - 0.005 × binder content (wt%) to C 化学量論量 (wt%) - up to 0.01 x binder content (wt%) It is particularly possible to provide for a range of

[0051] In the context of the present invention, the abovementioned advantageous effects are particularly pronounced in the case of coarse-grained hard alloys. In one preferred variant of the invention, it is therefore provided that the dispersed tungsten carbide is present in the cemented carbide material in the form of grains whose average grain size, measured according to DIN ISO 4499 Part 2, is in the range from 1 to 15 μm, advantageously in the range from 1.3 to 10 μm, particularly preferably in the range from 2.5 to 6 μm.

[0052] Advantageously, it is provided that the maximum proportion of Fe in the binding phase is 5% by weight and / or that other unavoidable impurities are present in the binder material.

[0053] If it is provided that the intermetallic phase (M,Y)3(Al,X), existing or formed by heat treatment or the action of heat, has the crystal structure L12 (space group 221) according to ICSD (Inorganic Crystal Structure Database), when the sintered carbide body is subjected to high loads, a microstructure of the binder phase arises in which the crystals of the intermetallic phase are able to effectively support each other in the metallic binder material.

[0054] Advantageously, and preferably for the application of earth excavation tools, it is provided that the intermetallic phase material existing or formed by heat treatment or the action of heat has a maximum size of 1500 nm, advantageously 1000 nm.

[0055] According to a preferred configuration variant of the invention, it can be provided that the cemented carbide material is free or as free as possible from eta phase and / or Al2O3. The inventors have realized that it is desirable for the maximum proportion of eta phase or the maximum proportion of Al2O3 to be at most 0.6% by volume relative to the total cemented carbide material. If both substances are present in the cemented carbide material, it is advantageous for the sum of eta phase material and Al2O3 to be at most 0.6% by volume.

[0056] The particle size of the Al2O3 and / or eta phase material is preferably at most 5 times the average particle size of WC, where the average particle size of WC and the particle size of the Al2O3 and / or eta phase material can be determined by the intercept method (in accordance with DIN ISO 4499 Part 2).

[0057] The toughness of cemented carbide materials can be adversely affected by the eta phase or by Al2O3. If the eta phase is present in a high proportion, cemented carbide materials are conditionally suitable for use in earth-digging tools where high demands are placed on them. The same is true for Al2O3.

[0058] The above-mentioned object of the present invention is also achieved by a tool, in particular a comminuting tool, an earth excavation tool, preferably for road mills, recyclers, stabilizers, agricultural or forestry earth excavators, which comprises a base body with a working area, in which at least one working element made of a sintered carbide material according to one of claims 1 to 17 is held, preferably by a material connection, in particular by a brazing connection, in particular by a hard brazing connection.

[0059] Advantageously, the cemented carbide material in the working area forms a cutting body having a cutting tip, blade or cutting edge or working edge. It is also conceivable that the cemented carbide material is a protective covering.

[0060] Thus, as mentioned above, it is possible according to the invention to provide that the working element is advantageously formed in the form of a cutting element having at least one blade and / or at least one cutting tip, or in the form of a wear protection element, in particular a protective plate, protective bar, protective pin, protective lug or protective bolt.

[0061] Particularly preferred applications of the present invention arise when it is provided that the tool is a cutting tool, a cutting chisel, in particular a road cutting chisel or a mining chisel, a ploughshare, a cultivator tip, a drill tool, in particular an earth drill, a crushing tool, for example a crushing chisel or a crushing bar, a mulching tool, a wood chipping tool or a shredder tool, a sorting tool, for example a screen.

[0062] A further particularly preferred use of the invention is in the form of a cutting chisel having a chisel head and a chisel shaft connected directly or indirectly thereto, the working element being held on the chisel head.

[0063] For example, it is possible to provide that the working element is formed by a cemented carbide material according to the invention, said working element forming a support for an ultra-hard cutting tip, for example made of PCD material.

[0064] As noted above, the cemented carbide material can be a hard alloy having a strengthening binder phase. This strengthening can be achieved by precipitation of intermetallic phase material during cooling in the sintering process and / or can be achieved when the intermetallic phase material is formed in a thermal process subsequent to the sintering process, where the cemented carbide material is brought to a temperature that allows for the precipitation of intermetallic phase material in the cemented carbide material.

[0065] For the production of the hard alloy according to the invention, the nominal composition of the raw materials at the initial weighing may be selected as follows: 70-95 wt. % WC, 1-28 wt. % metallic binder and 1-28 wt. % intermetallic phase. The metallic binder may contain the element Co, and optionally Fe and / or other components. The intermetallic phase is Ni3Al at the initial weighing.

[0066] The subject of the invention is also a method for producing a cemented carbide material, which comprises in a first method step producing a cemented carbide material precursor, in particular a hard alloy, which comprises 70-95% by weight, preferably 80-95% by weight, of tungsten carbide in dispersed form and a binder phase, the binder phase comprising a metallic binder material which comprises Co and which comprises the dissolved elements Ni and Al, the binder phase having the following chemical element composition: Ni>25wt%, Al>4wt%, balance Co and dissolved binder components such as W and / or C and in a further method step subjecting the cemented carbide material precursor to a heat treatment to form a cemented carbide material comprising an intermetallic phase material in a binder phase, wherein the intermetallic phase material is formed according to the structural formula (M,Y)3(Al,X), where M=Ni, Y=Co and / or other components, and X=tungsten and / or other components.

[0067] Here, the heat treatment can include at least one heating step or at least one cooling step.

[0068] According to the invention it is advantageously possible to provide that after the heat treatment at least a part of the crystals of the intermetallic phase material (M,Y)3(Al,X) has the crystal structure L12 (space group 221) according to ICSD (Inorganic Crystal Structure Database).

[0069] In order to be able to achieve a particularly effective strengthening of the binder phase, in particular in coarse-grained hard alloys as cemented carbide materials, it is advantageously possible to provide that at least a portion of the intermetallic phase material has a maximum size of 1500 nm, advantageously 1000 nm (measured by the section method on microscopic specimens).

[0070] Advantageously, it can be provided that the coercivity HcM of at least one region of the cemented carbide material produced by the method according to the invention, advantageously in the region where the intermetallic phase material is present, is: HcM[kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+4[kA / m], Advantageously, HcM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+6 [kA / m]; Particularly preferably, HcM [kA / m]>(1.5+0.04×B)+(12.5−0.5×B) / D+10 [kA / m] where B is the proportion of binder phase in the cemented carbide material (% by weight) and D is the grain size of the dispersed WC determined by the intercept method according to DIN ISO 4499 Part 2.

[0071] For typical hard alloys containing Co in the binder phase and no intermetallic phase material, the coercivity is usually used to indirectly determine the average grain size of WC at a given binder content. According to the present invention, the intermetallic phase material significantly increases the coercivity. Thus, the coercivity can be indirectly evaluated as an indicator of the strengthening of the binder phase by the intercalated intermetallic phase material. The higher the coercivity, the greater the sum of the interfaces between the metal binder material, the intermetallic phase material and WC. The greater the number of precipitated intermetallic phase materials, the better the support of the individual crystals of the intermetallic phase material to each other in the binder phase, especially at high temperatures (especially at high tool use temperatures).

[0072] The coercivity HCM [kA / m]>(1.5+0.04×B)+(12.5−0.5×B) / D+4 [kA / m] of at least one region of the cemented carbide material can be used primarily for the above-mentioned wear protection applications, e.g. wear protection.

[0073] The coercivity of at least one region of the sintered carbide material, advantageously HCM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+6 [kA / m], can be used primarily in earth-digging tools where high demands are imposed, as mentioned above.

[0074] The coercivity of at least one region of the cemented carbide material, advantageously HCM [kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+10 [kA / m], can be used primarily for the above mentioned high performance tools.

[0075] According to one configuration variant of the invention, it can also be provided that the coercivity of at least one region of the cemented carbide material is 20% higher than the coercivity of a hard alloy body having the same composition and WC grain size as the cemented carbide material, wherein the binder phase is formed exclusively from a metallic Co binder, which does not contain any intermetallic phase material.

[0076] Thus, a hard alloy body having the same composition is a hard alloy body comprising 70-95% by weight of dispersed tungsten carbide and a binder phase, the binder phase comprising a metallic binder material but no intermetallic phase material, the proportion of metallic binder material in the cemented carbide material being 5-30% by weight, the binder material otherwise having the same or nearly the same composition as the binder material of the cemented carbide material according to the invention.

[0077] As discussed above, the coercivity indirectly indicates the proportion of intermetallic phase material in the binder phase, and therefore the degree of strengthening of the binder phase.

[0078] Within the scope of the present invention, the sintered carbide material produced by the method according to the invention can be configured such that the sintered carbide material has a hot compressive strength of ≥ 1650 MPa at a temperature of 800 ° C and a strain rate of 0.001 [1 / s] and / or such that the sintered carbide material has a hot compressive strength of ≥ 1600 MPa at a temperature of 800 ° C and a strain rate of 0.01 [1 / s] (measured on cylindrical test pieces with a diameter of 8 mm and a height of 12 mm). With a sintered carbide material in which the proportion of metal binder material in the binding phase is 5-7% by weight and the proportion of WC is in the range of 93-95% by weight, advantageously in which case WC is present in the form of coarse grains with an average grain size in the range of 2-5 μm, cutting tips, in particular for road cutting chisels, can be produced.

[0079] Manufacturing (including explanation of measurement methods) Manufacturing: The following describes how cemented carbide materials containing intermetallic phase material in the binder phase can be produced by a powder metallurgy process routine, which is divided into the process steps of producing a pressable powder mixture, compacting, and finally sintering to obtain a compact dense cemented carbide body.

[0080] As starting material for the production of the powder mixture, WC powders of various grain sizes can be used, in particular coarse-grained WC with a grain size FSSS>25 μm. The starting powders for the binder phase are ultrafine-grained cobalt powder (FSSS 1.3 μm) and nickel aluminum powder, for example Ni-13Al powder with an aluminum content of about 13.3% by weight. The grain size of the Ni-Al powder is FSSS<70 μm, preferably FSSS<45 μm. To adjust and balance the targeted carbon content, W metal powder (FSSS<2 μm) and carbon black are used. For alloying the binder phase with alloying elements such as Ti, Ta, Mo, Nb, V, Cr, their carbide powders or W-containing mixed carbides with a grain size <3 μm are used.

[0081] The powder mixture is produced by wet grinding according to the prior art, preferably in a ball mill equipped with hard alloy balls. As grinding media, ethanol and hexane are used. Other possible grinding media would be acetone, or an aqueous medium containing suitable inhibitors.

[0082] For the production of powder mixtures of cemented carbide materials with binder contents >15%, a single grinding step is sufficient due to the high binder content and enhanced recrystallization, whereas for binder contents below 15%, a multi-stage wet grinding process is advantageous to effectively grind the Ni-Al powder and minimize oxide formation during the grinding process.

[0083] In the first method step, the Ni-Al powder is intensively mixed with the grinding liquid and coarse-grained tungsten carbide with an average grain size FSSS>20 μm, preferably 30-60 μm. If necessary, pressing aids, small amounts of alloying components and cobalt powder can already be added here.

[0084] The grinding parameters (time, ratio of grinding balls to grinding material, grinding media) and the ratio of WC to Ni-Al powder vary depending on the WC grain size set in the cemented carbide material.

[0085] In a second method step, 50-80% by weight of WC raw material of a given particle size is added to this pre-grind and mixed, with the main focus being on reducing agglomerates and obtaining as homogeneous a mixture as possible.

[0086] If alloy adjustment and addition of pressing aid have not already been carried out in the first grinding step (pre-grinding VM), this can also be carried out in a second method step.

[0087] The slurry obtained from the wet milling is dried by conventional techniques and converted into a powder suitable for pressing, preferably by the spray drying process.

[0088] The forming is preferably carried out directly by axial pressing in a mechanical, hydraulic or electromechanical press.

[0089] Sintering is carried out in vacuum at 1350-1550° C., preferably in industrial sintering-HIP furnaces, in which an overpressure is generated after liquid phase sintering by introducing an inert gas, in which any residual porosity present can be eliminated.

[0090] FIG. 1 shows an exemplary phase diagram of WC-Co-Ni3Al for 3 wt. % Co and 3 wt. % Ni3Al, which illustrates the formation of these precipitates.

[0091] After solidification of the melt, initially only WC and a solid solution of Co, Ni, Al, W and C are present. Only below the solvus temperature do intermetallic phase materials precipitate out of this solid solution, preferably formed according to the structural formula (M,Y)3(Al,X), where M=Ni, Y=Co and / or other elements, and X=tungsten and / or other elements. These intermetallic phase materials can be visible with a scanning electron microscope.

[0092] In Figures 2 and 3 two different cemented carbide materials according to the invention in the form of hard alloys are shown by such scanning electron microscope images. The binder phase of such hard alloys can be clearly seen and the intermetallic phase material (light phase) 10 and the metallic binder material 30 (dark) can be distinguished. The WC grains 20 are bonded to each other via the binder phase.

[0093] It is found that the intermetallic phase material is uniformly distributed in the binder phase, with the crystals of the intermetallic phase material having a cubic shape and preferably smaller than 1500 nm. The crystals of the intermetallic phase material (M,Y)3(Al,X) have the crystal structure L12 (space group 221) according to ICSD (Inorganic Crystal Structure Database).

[0094] Such sintered carbide materials can be bonded to a steel substrate, whereby they form a working element of a tool, for example a grinding tool, an earth excavation tool, preferably for a road mill, a recycler, a stabilizer, an agricultural or forestry earth excavator. In this case, the working element is arranged in the working area of ​​the tool. The joining to the substrate is carried out by a brazing joint, in particular by a hard brazing joint. In this case, heat is applied to the tool in order to form the brazing joint. The tool is then quenched, for example in a water and oil emulsion.

[0095] The brazing process at least partially re-melts the intermetallic phase material such that each component of the intermetallic phase material is present as a dissolved component in the cemented carbide material after quench hardening, thus forming a cemented carbide material precursor.

[0096] This cemented carbide material precursor is then subjected to a heat treatment, as already mentioned above in several instances, whereby heat can be introduced into the cemented carbide material, the temperature being below the solvus temperature and preferably above 400° C. The treatment time, i.e. the time during which the heat treatment is carried out, is between 0.25 and 24 hours. Intermetallic phase material is again formed in at least some regions of the cemented carbide material during the heat treatment, resulting in a strengthening of the binder phase.

[0097] Here, the heat treatment can be an active process in which heat is introduced into the sintered carbide material in a targeted manner using a heat source. Advantageously, the heat treatment is carried out passively, for example when the sintered carbide material precursor comes into contact with a workpiece, for example a road surface, during use of the tool. During this contact, heat is introduced into the sintered carbide material precursor, bringing it to a temperature at which the intermetallic phase material is formed. In this way, the tool is automatically strengthened according to the invention, with the sintered carbide material according to the invention being formed in the areas subject to wear.

[0098] It is also conceivable that the cemented carbide material configured as described above is produced by a sintering process, during which the intermetallic phase is formed. The product can then be advantageously brought to a temperature above the solvus temperature at which the intermetallic phase at least partially re-dissolves. The material is then quenched to form a cemented carbide material precursor. The cemented carbide material precursor is then subjected to a heat treatment to form the cemented carbide material according to the invention.

[0099] In order to allow easy precipitation of the intermetallic phase material in the binder phase, it can be advantageously provided that the (M,Y)3(Al,X) content in the binder phase is ≧40%, with the carbon proportion being adjusted to be stoichiometric or less than stoichiometric.

[0100] It was found that the higher the tungsten dissolution in the binder phase, the more stable the precipitation of the intermetallic phase was, because the precipitation range shifted to higher temperatures as "Co3W" was incorporated into the crystal structure of the intermetallic phase material.

[0101] Here the elements Mo, Nb, Cr, V and especially Ti, Ta show a similar effect and can be added to the alloy in small amounts (<15 at % in the binder).

[0102] The amount of alloy that can be used depends on the solubility product of each of the metal carbides. Even if its magnitude is negligible, a surprisingly clear effect has been shown that is not due to a grain refinement effect.

[0103] Based on the improved stability and precipitation behavior, the addition of other elements to the alloy allows the percentage of intermetallic phase material in the binder to be reduced, even below 40%. Furthermore, in the presence of, for example, Ti and Ta, these elements take over the role of tungsten as a stabilizer, making it unnecessary to adjust the carbon percentage below the stoichiometric amount.

[0104] The effect of the precipitation of intermetallic phase materials on hot strength can be impressively demonstrated by hot compression tests. Figure 4 shows the hot compression strength of a hard alloy containing 6% binder at different test temperatures and strain rates. Especially at the test temperature of 800°C, the strength increases by about 40-50% due to the intermetallic phase materials.

[0105] Physical property values ​​were measured on samples of the cemented carbide material according to the invention and serve to characterize the material and its properties.

[0106] In the case of hard alloys, the coercive force H cM Measurement of the specific saturation magnetization of 4 ps has been established as a non-destructive testing method.

[0107] Both measurement parameters are also determined for the characterization of the cemented carbide material according to the invention with Förster Koerzimat® 1.097.

[0108] Another parameter for the characterization of materials is density, which is determined by weighing according to Archimedes' principle.

[0109] The hardness of the blanks is determined on metallographically prepared polished specimens of hard alloys in accordance with valid standards, advantageously using the Vickers HV10 hardness test with a test load of 10 kp (ISO 3878).

[0110] Similarly, the porosity (DIN-ISO 4499-4 standard) and aluminium oxide particles of the sintered material are checked and evaluated by optical microscopy on the polished samples. Comparative images of A or B porosity can be used to estimate the volume percentage of aluminium oxide in the microstructure, where A08 or B08 corresponds to a volume percentage of approximately 0.6 volume %. For optical microscopy examination of the eta phase, this is etched with Murakami's reagent according to the standard (DIN-ISO 4499-4). The average grain size of the WC is determined according to DIN ISO 4499-2. In this case, SEM (scanning electron microscope) images are evaluated by sectioning.

[0111] The proportion of intermetallic phases in the binder and the maximum size of the precipitated particles are also determined by SEM images, but using an in-lens BSE detector. For this purpose, images are taken at several points of the sample and an evaluation is carried out on representative cross sections by image processing and determination of the area proportion by gray scale division.

[0112] Working Example: The following table shows examples of sintered carbonized bodies according to the invention, which in principle can be produced by the same methods as described above: [Table 1]

[0113] [Table 2-1] [Table 2-2] [Table 2-3]

[0114] Thus, in accordance with the above explanation, the present invention relates to a sintered carbide material, in particular a hard alloy, comprising 70-95% by weight, advantageously 80-95% by weight, of tungsten carbide in dispersed form and a binder phase, the binder phase comprising a metallic binder material which comprises Co, dissolved Ni and dissolved Al, the binder phase optionally comprising an intermetallic phase material, if present, being formed according to the structural formula (M,Y)3(Al,X), where M=Ni, Y=Co and / or other components, X=tungsten and / or other components, the binder phase having the following chemical element composition: Ni>25% by weight, Al>4% by weight, balance Co and dissolved binder components, e.g. W and / or C.

[0115] The invention will now be described in more detail with reference to example embodiments shown in FIGS. [Brief description of the drawings]

[0116] [Figure 1] FIG. 1 is a phase diagram of WC—Co—Ni3Al for 3 wt.% Co and 3 wt.% Ni3Al. [Diagram 2] FIG. 1 shows a cemented carbide material according to the invention in the form of a hard alloy. [Diagram 3] FIG. 1 shows a cemented carbide material according to the invention in the form of a hard alloy. [Figure 4] FIG. 1 is a diagram showing the hot compressive strength of a hard alloy containing 6% binder when the test temperature and strain rate are changed. [Diagram 5] FIG. 2 is a vertical cross-sectional view of the chisel tip. [Figure 6] 6 shows the chisel tip according to FIG. 5 along the section line marked VI-VI in FIG. 5. [Figure 7] FIG. 7 is a vertical cross-sectional view of a chisel tip 50 according to FIGS. 5-6, but with a modified texture. [Figure 8] FIG. 7 is a vertical cross-sectional view of a chisel tip 50 according to FIGS. 5-6, but with a modified texture. [Figure 9] FIG. 7 is a vertical cross-sectional view of a chisel tip 50 according to FIGS. 5-6, but with a modified texture. [Figure 10] FIG. 7 is a vertical cross-sectional view of a chisel tip 50 according to FIGS. 5-6, but with a modified texture. [Figure 11] FIG. 7 is a vertical cross-sectional view of a chisel tip 50 according to FIGS. 5-6, but with a modified texture. [Figure 12] FIG. 7 is a vertical cross-sectional view of a chisel tip 50 according to FIGS. 5-6, but with a modified texture.

[0117] Figures 5 to 12 show chisel tips 50 in the form of cemented carbide material 40. These chisel tips 50 are preferably used in cutting tools, in particular cutting chisels, round shank chisels, road cutting chisels, mining chisels and the like.

[0118] The chisel tip 50 is formed and prepared to be joined, preferably brazed, to a steel body. For this purpose, the steel body usually has a head with an integrally molded shank, preferably a round shank. Towards the direction away from the shank, the head has a receptacle for the chisel tip 50. The chisel tip 50 can be fixed in or on this receptacle.

[0119] The chisel tip 50 is of one-piece construction and has a base part 51 by means of which the chisel tip 50 can be joined to a steel body. Advantageously, the base part 51 has a joining surface 51.1. In order to fasten the chisel tip 50 to the steel body, a brazing material of a hard brazing joint can be arranged between the joining surface 51.1 and the steel body.

[0120] In order to keep the thickness of the brazing gap between the chisel tip 50 and the steel body as constant as possible, it can be provided that a spacer 51.2 is molded on the chisel tip 50 in the area of ​​the joining surface 51.1, which spacer 51.2 is formed so as to protrude beyond the joining surface 51.1 and rest on the steel body in such a way that the joining surface 51.1 is held at a distance from the mating surface of the steel body for the brazing process.

[0121] It can furthermore be provided that one or more recesses 52 are present in the region of the joining surface 51.1, which can advantageously be configured to transition via a convex radius of the joining surface 51.1 into a concave portion, which is preferably formed as a concave valley. The recesses 52 make it possible to reduce the material required for the chisel tip 50. Furthermore, the recesses 52 form a reservoir for excess brazing material in the region of the joining surface 51.1.

[0122] The base portion 51 preferably has a circumferential edge 51.3, which may be formed as a convex shape at least in some areas, and the edge 51.3 may be formed as a transition portion between the base portion 51 and the transition portion 53.

[0123] The transition 53 has a first region formed as a concave region 53.1. A truncated pyramidal geometry or a combination of the concave region 53.1 and an at least partially truncated pyramidal geometry may also be provided. The first region causes the chisel tip 50 to taper in a direction from the base 51 towards the tip 54 of the chisel tip 50.

[0124] The transition 53 may furthermore have a cylindrical region 53.2 which continues to the first region on the opposite side of the base portion 51. As shown in Fig. 5, at least in the region of the chisel tip 50, the transition between the first region and the cylindrical region is made continuously, preferably continuously differentiable in the direction of the longitudinal central axis of the chisel tip, so that a break in continuity is avoided.

[0125] The chisel tip 50 can advantageously have depressions 53.3 in the region of the transition 53. These serve to reduce material and to optimise the evacuation of the soil material that is undermined during use of the tool.

[0126] The chisel tip 50 has a tip 54 which is preferably continuous with a cylindrical region 53.2 at the transition 53. The connection 54.1 can be formed as a convex bend. The connection 54.1 is followed by a tapered section 54.2 which merges into an end section 54.3. The end section 54.3 is preferably formed in the form of a convex bend, particularly preferably in the form of a spherical cap.

[0127] 6 shows a cross-sectional view and a top view of the chisel tip 50. The indentations 53.3, which are arranged in a uniform distribution over the circumference of the chisel tip 50, are clearly visible.

[0128] The chisel tip 50 has at least one first volume region 70 and at least one second volume region 60 .

[0129] In the second volume region 60, the cemented carbide material 40 comprises tungsten carbide grains (WC grains) 20 which are bonded to one another via a metal binder material 30 of the bonding phase. It can be provided that in the second volume region 60, no intermetallic phase material 10 is present or that the intermetallic phase material 10 is present in a concentration advantageously less than 30% by weight / unit volume, advantageously less than 25% by weight / unit volume, particularly preferably less than 15% by weight / unit volume.

[0130] In the first volume region 70, the cemented carbide material 40 comprises tungsten carbide grains (WC grains) 20 which are bonded to one another via a metal binder material 30 of the bonding phase. In the first volume region 70, the intermetallic phase material 10 is advantageously present in a concentration of ≧30% by weight / unit volume, advantageously in the range of 30-70% by weight / unit volume, particularly preferably in the range of 35-60% by weight / unit volume, even more preferably in the range of 40-50% by weight / unit volume.

[0131] The intermetallic phase material is formed according to the structural formula (M,Y)3(Al,X), where M=Ni, Y=Co and / or other elements, and X=Tungsten and / or other elements. The binder phase has the following chemical element composition: Ni>25 wt%, Al>4 wt%, balance Co and dissolved binder elements such as W and / or C.

[0132] The relative proportion Y of intermetallic phase material per unit volume in the first volumetric region 70 is greater than in the second volumetric region 60 .

[0133] As shown in the drawings, the first volumetric region 70 and the second volumetric region 60 may border at least one region of a surface of the cemented carbide material 40 .

[0134] The first volumetric region 70 having a higher relative proportion of intermetallic phase material 10 forms part of the surface of the chisel tip 50, particularly the tip 54 of the tapered portion 54.2 and / or the terminal portion 54.3.

[0135] Starting from the tip 54, the first volume region 70 may also extend further up to the base 51. Advantageously, the region of the base 51 may also be formed by the second volume region 60. The second volume region 60, which has a relatively low content of intermetallic phase material 10 or is free of intermetallic phase material 10, is advantageously arranged in the region of the transition 53. As shown in FIG. 6, both the first volume region 70 and the second volume region 60 may also adjoin the surface of the chisel tip 50 in the region of the transition 53.

[0136] The arrangement of the first and second volumetric regions 70, 60 according to the example embodiment shown in Figures 5 and 6 has the following technical advantages: The tip 54 being formed by the first volume region 70 provides in this case a high resistance to wear, particularly in areas at risk of wear.

[0137] In areas where there is no risk of wear, the toughness and therefore the fracture stability is improved.

[0138] It is further envisaged that the volume regions 60, 70 allow targeted adjustment of a particular wear regime, for example aiding in the resharpening of the chisel tip.

[0139] Figures 7 to 12 show further configuration variants of the chisel tip 50. Here, the chisel tip 50 is configured essentially identically to the chisel tip 50 shown in Figures 5 and 6. In this respect, reference is made to the above description in order to avoid repetition, and only the differences are described. The chisel tip 50 according to Figures 7 to 12 differs in particular in the arrangement and configuration of the first and second volume regions 70, 60.

[0140] As shown in Fig. 7, the first volume 70 is arranged in the region of the tip 54, preferably partially in the cylindrical region 53.2 of the transition part 53. However, it is also conceivable that the first volume 70 is arranged only in the region of the tip 54. In that case, the first volume 70 effectively protects against wear and abrasion in the region of the tip 54.

[0141] 8 shows that the first volume region 70 can be arranged completely or partially in the chisel tip 50. The first volume region 70 can in this case be configured to extend in the direction of the longitudinal central axis of the chisel tip 50, advantageously over the entire region of the transition 53. As already mentioned above, the first volume region 70 is characterized by a particularly high shear strength due to the presence of the intermetallic phase material 10. In this way, the transition region 53, which is at risk of fracture, is effectively reinforced by the first volume region 70.

[0142] Conversely, it is also possible to arrange the second volume area 60 completely or partially within the chisel tip 50, as shown in Fig. 9. In this case, the first volume area 70 advantageously completely surrounds the second volume area 60. To provide a particularly effective protection against wear and against breakage of the chisel tip 50 in the region of the transition 53, the first volume area completely or almost completely forms the surface of the chisel tip 50. Due to its large extent transverse to the longitudinal central axis of the chisel tip 50, the first volume area 70 also provides a high axial bending resistance moment.

[0143] Figure 10 shows that in a development of the variant according to Figure 7, the first volume region 70 with a high relative proportion of intermetallic phase material 10 can extend beyond the region of the tip 54 and the transition 53, whereby the first volume region 70 may advantageously completely form the surfaces of the tip 54 and the transition. The first volume region 70 can also be led up to or into the base 51, as shown in Figure 10.

[0144] FIG. 11 shows that the first volume region 70 may extend within the chisel tip 50 from the distal end 54.3 of the tip 54 to the base portion 51 to form a continuous volume region.

[0145] FIG. 12 shows that, contrary to the example embodiment according to FIGS. 5 and 6, it is also possible to provide that the first and second volume regions 70, 60 are interchanged.

[0146] The above figures should be understood as schematic illustrations, especially when the first or second volume regions 70, 60 are not precisely sharply defined as shown in the figures, but rather a transition is formed between the two volume regions 70, 60.

[0147] To produce or form the cemented carbide material 40 shown in Figures 5 to 12, according to the invention, a method is first used in a first method step to produce a cemented carbide material precursor, in particular a hard alloy, which comprises 70-95 wt. %, advantageously 80-95 wt. %, of tungsten carbide in dispersed form and a binder phase. The binder phase comprises at least Co as metallic binder material and also the dissolved elements Ni and Al. The binder phase has the following chemical element composition: Ni>25wt%, Al>4wt%, balance Co and dissolved binder components such as W and / or C has.

[0148] In a further method step, the cemented carbide material precursor is subjected to a heat treatment as described above to form a cemented carbide material 40 including an intermetallic phase material 10 in a binder phase in at least a first volumetric region 70. The intermetallic phase material 10 is formed according to the structural formula (M,Y)3(Al,X), where M=Ni, Y=Co and / or other elements, and X=tungsten and / or other elements.

[0149] For this purpose, in a further method step, the sintered carbide material precursor can be held during a heat treatment in a temperature range between 400° C. and the solvus temperature for a period of 0.25 to 12 h. For the targeted formation of the individual volume regions 60, 70, the targeted heating can be carried out, for example, by means of a laser or an induction coil.

Claims

1. A cemented carbide material (40), in particular a hard alloy, comprising 70-95% by weight, preferably 80-95% by weight, of tungsten carbide in dispersed form and a binder phase, said binder phase comprising a metallic binder material (30), said metallic binder material comprising Co, said binder phase comprising an intermetallic phase material (10) and / or the dissolved elements Ni and Al, said intermetallic phase material (10), if present, having the structural formula (M,X) 3 (Al,Y), where M=Ni, Y=Co and / or other elements, and X=Tungsten and / or other elements, said binder phase having the following chemical element composition: Ni>25 wt%, Al>4 wt%, balance Co and dissolved binder components such as W and / or C A cemented carbide material (40).

2. The binder phase has the following chemical element composition: Ni>35 wt.%, Al>5 wt.%, balance Co and dissolved binder components such as W and / or C; Particularly preferred is a composition containing Ni>40 wt.%, Al>6.5 wt.%, the remainder Co and dissolved binder components such as W and / or C. The cemented carbide material (40) of claim 1, having a

3. 3. The cemented carbide material (40) according to claim 1 or 2, wherein the ratio of the weight percentage of Al to the weight percentage of Ni is >0.10, preferably >0.

12.

4. The cemented carbide material (40) according to claim 1 or 2, wherein the proportion of Co in the cemented carbide material (40) is between 1 and 28% by weight, preferably between 1 and 19% by weight.

5. 3. The cemented carbide material according to claim 1 or 2, wherein the sum of the elements Ni and Al in the cemented carbide material (40) is between 1 and 28% by weight, preferably between 1.5 and 19% by weight, at least in certain areas of the cemented carbide body.

6. 3. The cemented carbide material of claim 1 or 2, wherein the cemented carbide material (40) has at least two volume regions (60, 70), and the relative proportion of intermetallic phase material (10) per unit volume in the first volume region (70) is greater than in the second volume region (60).

7. said first volume region (70) borders on at least one region of the surface of said cemented carbide material (40), and advantageously said second volume region (60) is not adjacent to a surface of said cemented carbide material (40), or The cemented carbide material (40) of claim 6, wherein the second volume region (60) borders at least one region of a surface of the cemented carbide material (40), and advantageously the first volume region (70) is not adjacent to a surface of the cemented carbide material (40).

8. 3. The cemented carbide material (40) according to claim 1 or 2, wherein the binder phase, in particular the metallic binder material (30) and / or the intermetallic phase material (10), comprises Nb and / or Ti and / or Ta and / or Mo and / or V and / or Cr, advantageously one or more of said materials being present in dissolved form in the binder phase.

9. 3. The cemented carbide material (40) of claim 1 or 2, wherein the carbon percentage in the cemented carbide material (40) is adjusted to be stoichiometric or less than stoichiometric.

10. The carbon percentage in the cemented carbide material (40) is C 化学量論量 (wt%)-0.003 x binder content (wt%) to C 化学量論量 (wt%) - 0.012 x binder content (wt%) and advantageously in the range C 化学量論量 (wt%)-0.005 x binder content (wt%) to C 化学量論量 (wt%) - up to 0.01 x binder content (wt%) The cemented carbide material (40) of claim 9, wherein the thermal expansion coefficient is in the range of

11. 3. The cemented carbide material (40) of claim 1 or 2, wherein the proportion of Mo and / or Nb and / or Ti and / or Ta and / or Cr and / or V in the binder phase is ≦15 at.%.

12. 3. The cemented carbide material (40) according to claim 1 or 2, wherein the dispersed tungsten carbide (WC grains 20) is present in the cemented carbide material (40) in the form of grains having an average grain size, measured in accordance with DIN ISO 4499 Part 2, in the range of 1 to 15 μm, preferably in the range of 1.3 to 10 μm, particularly preferably in the range of 2.5 to 6 μm.

13. 3. The cemented carbide material (40) of claim 1 or 2, wherein the maximum proportion of Fe in the binder phase is <5 wt. % and / or other unavoidable impurities are present in the binder phase.

14. The intermetallic compound phase material (M, Y) 3 3. The cemented carbide material (40) according to claim 1 or 2, wherein at least some of the crystals of (Al,X) (10) have the crystal structure L12 (space group 221) according to ICSD (Inorganic Crystal Structure Database).

15. 3. The cemented carbide material (40) of claim 1 or 2, wherein at least a portion of the intermetallic phase material (10) has a maximum size (measured by sectioning on microscopic specimens) of 1500 nm, preferably 1000 nm.

16. Maximum proportion of eta phase or Al 2 O 3 or the maximum proportion of Al is at most 0.6% by volume relative to the total of the cemented carbide material (40), or the eta phase material and Al 2 O 3 The cemented carbide material (40) of claim 1 or 2, wherein the sum of is at most 0.6 volume percent.

17. A 2 O 3 and / or the average grain size of the eta phase material is at most 5 times the average grain size of the WC.

18. The coercive force HcM of at least one region of the cemented carbide material (40) produced by the method according to the invention is: HcM[kA / m]>(1.5+0.04×B)+(12.5-0.5×B) / D+4[kA / m], Advantageously, HcM [kA / m] > (1.5 + 0.04 × B) + (12.5 - 0.5 × B) / D + 6 [kA / m], Particularly preferably, HcM [kA / m]>(1.5+0.04×B)+(12.5−0.5×B) / D+10 [kA / m] 3. The cemented carbide material (40) according to claim 1 or 2, wherein B is the proportion (wt.%) of the binder phase in the cemented carbide material and D is the grain size of the dispersed WC determined by the intercept method according to DIN ISO 4499 Part 2.

19. 1. A tool, in particular a comminuting tool, an earth excavation tool, preferably for a road mill, for a recycler, for a stabilizer, for an agricultural or forestry earth excavator, comprising a base body with a working area, in which at least one working element made of a sintered carbide material (40) according to claim 1 or 2 is held, preferably by a material joint, in particular by a brazing joint, in particular by a hard brazing joint.

20. 20. The tool according to claim 19, wherein the working element is preferably in the form of a cutting element having at least one cutting edge and / or at least one cutting tip or in the form of a wear protection element, in particular a protective plate, protective bar, protective pin, protective lug or protective bolt.

21. 20. The tool according to claim 19, wherein the tool is a cutting tool, a cutting chisel, in particular a road cutting chisel or a mining chisel, a ploughshare, a cultivator tip, a drill tool, in particular an earth drill, a crushing tool, for example a crushing chisel or a crushing bar, a mulching tool, a wood chipping tool or a shredder tool, a sorting tool, for example a screen.

22. 22. The tool of claim 21, wherein the cutting chisel comprises a chisel head and a chisel shaft directly or indirectly connected thereto, the working element being carried by the chisel head.

23. A method for producing a cemented carbide material (40), comprising the steps of: in a first method step producing a cemented carbide material precursor, in particular a hard alloy, which comprises 70-95% by weight, preferably 80-95% by weight, of tungsten carbide in dispersed form and a binder phase, said binder phase comprising a metallic binder material (30) which comprises Co, said metallic binder material (30) comprising the dissolved elements Ni and Al, said binder phase having the following chemical element composition: Ni>25 wt%, Al>4 wt%, balance Co and dissolved binder components such as W and / or C and in a further method step, subjecting the cemented carbide material precursor to a heat treatment to form a cemented carbide material (40) comprising an intermetallic phase material (10) in the binder phase, wherein the intermetallic phase material (10) has the structural formula (M,Y): 3 (Al,X) where M=Ni, Y=Co and / or other elements, and X=Tungsten and / or other elements.

24. The intermetallic compound phase material (M, Y) 3 24. The method of claim 23, wherein at least a portion of the crystal of (Al,X)(10) has the crystal structure L12 (space group 221) according to the Inorganic Crystal Structure Database (ICSD).

25. 25. The method according to claim 23 or 24, wherein at least a portion of the intermetallic phase material (10) has a maximum size (measured by sectioning on a microscopic specimen) of 1500 nm, preferably 1000 nm.

26. 25. The method of claim 23 or 24, wherein the cemented carbide material precursor is held during the heat treatment at a temperature ranging between 400° C. and the solvus temperature for a period ranging from 0.25 to 24 hours.

27. The method of claim 23 or 24, wherein the cemented carbide material precursor is formed as the cemented carbide material (40) of claim 1 or 2.